2011
DOI: 10.4090/juee.2011.v5n2.073083
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Urban Sprawl in Londrina, Paraná, Brazil

Abstract: Abstract:Public policies encouraging the insertion of large industrial and commercial developments near highways, associated to exclusionary housing policies, have shaped over the past decades a new urbanization phenomenon; the sprawl. This is largely characterized by discontinuous and fragmented occupation, with random population densities. This phenomenon brings environmental and social impacts to the urban and rural population, in addition to a great burden for the Government. In line with this and consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…People employed in industrial sector, due to high costs of commuting; prefer to settle in locations close to industrial quarter, which in effect increases the density. In relevant literature it has been noted that the development of industry and commerce in regions closer to highways played role in the development of new settlements and formation of urban sprawl phenomenon (Patacchini, Zenou, Henderson, & Epple, 2009;Polidoro et al, 2011). It is also stated that industrial and correspondingly housing sector shifted towards city outskirts to select low-value farmlands which in effect transformed farmlands into urban lands and created urban sprawling (Du et al, 2013;Malaque III & Yokohari, 2007), as also been verified in current study.…”
Section: Nominal Value For Farmland/urban Land In Sprawl Areassupporting
confidence: 77%
See 1 more Smart Citation
“…People employed in industrial sector, due to high costs of commuting; prefer to settle in locations close to industrial quarter, which in effect increases the density. In relevant literature it has been noted that the development of industry and commerce in regions closer to highways played role in the development of new settlements and formation of urban sprawl phenomenon (Patacchini, Zenou, Henderson, & Epple, 2009;Polidoro et al, 2011). It is also stated that industrial and correspondingly housing sector shifted towards city outskirts to select low-value farmlands which in effect transformed farmlands into urban lands and created urban sprawling (Du et al, 2013;Malaque III & Yokohari, 2007), as also been verified in current study.…”
Section: Nominal Value For Farmland/urban Land In Sprawl Areassupporting
confidence: 77%
“…Practices of public policies which support industrial and business development close to highway depending on dwelling policies revealed sprawl which is a new phenomenon of urbanization (Polidoro, de Lollo, & Barros, 2011). Urbanized areas which have sprawled towards outskirts rapidly with the aim of dwelling, industry and trade in USA towards the end of 1950's resulted in occupation of forests.…”
Section: Land Use Change and Urban Sprawlmentioning
confidence: 99%
“…A large part of the studies on urban sprawl is mainly related to the cities of developed countries, and among the developing countries, Chinese cities take first place in the ranking. The most influential factors on urban sprawl in the researches including: political fragmentation (Bhatta, ; Burchfield et al, ; Byun & Esparza, ; Christiansen & Loftsgarden, ; EEA, ; Pendall, ), land value (EEA, ; Christiansen & Loftsgarden, ; Habibi & Asadi, ; Pendall, ; Zhang, ), role of public policy & local government (Milan & Creutzig, ; Pendall, ; Polidoro, de Lollo, & Barros, ; Zhang, ;), population growth (Bhatta, ; Christiansen & Loftsgarden, ; EEA, ; Habibi & Asadi, ; Lata, Rao, Prasad, Badarianth, & Rahgavasamy, ; Zhang & Su, ), economic growth (Bhatta, ; Christiansen & Loftsgarden, ; EEA, ; Habibi & Asadi, ; Lata et al, ; Milan & Creutzig, ; Zhang & Su, ), policies on urban land use (Bhatta, ; Burchell et al, ; Christiansen & Loftsgarden, ; Pendall, ), Transportation (Bhatta, ; Burchfield et al, ; Christiansen & Loftsgarden, ; EEA, ; Ewing, ; Habibi & Asadi, ; Weilenmann, Seidl, & Schulz, ; Zhang & Su, ), industrialization (Bhatta, ; Burchfield et al, ; Yue et al, ; Zhang & Su, ), land speculation (Bhatta, ; EEA, ; Ewing, ), property tax (Bhatta, ; Song & Zenou, ; Wassmer, ), preferences of consumer (Bhatta, ; Christiansen & Loftsgarden, ; EEA, ; Ewing, ; Habibi & Asadi, ), problems of inner cit...…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large part of the studies on urban sprawl is mainly related to the cities of developed countries, and among the developing countries, Chinese cities take first place in the ranking. The most influential factors on urban sprawl in the researches including: political fragmentation (Bhatta, 2010;Burchfield et al, 2006;Byun & Esparza, 2005;Christiansen & Loftsgarden, 2011;EEA, 2006;Pendall, 1999), land value (EEA, 2006;Christiansen & Loftsgarden, 2011;Habibi & Asadi, 2011;Pendall, 1999;Zhang, 2000), role of public policy & local government (Milan & Creutzig, 2016;Pendall, 1999;Polidoro, de Lollo, & Barros, 2011;Zhang, 2000;), population growth (Bhatta, 2010;Christiansen & Loftsgarden, 2011;EEA, 2006;Habibi & Asadi, 2011;Lata, Rao, Prasad, Badarianth, & Rahgavasamy, 2001;Zhang & Su, 2016), economic growth (Bhatta, 2010;Christiansen & Loftsgarden, 2011;EEA, 2006;Habibi & Asadi, 2011;Lata et al, 2001;Milan & Creutzig, 2016;Zhang & Su, 2016), policies on urban land use (Bhatta, 2010;Burchell et al, 1998;Christiansen & Loftsgarden, 2011;Pendall, 1999), Transportation (Bhatta, 2010;Burchfield et al, 2006;Christiansen & Loftsgarden, 2011;EEA, 2006;Ewing, 2008;…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is the case cited byPolidoro et al (2012) for the city of Londrina, in Parana.5 An Intermediate City in Brazil: Between Inequalities and Growth…”
mentioning
confidence: 93%